Moral distress and Burnout syndrome: are there relationships between these phenomena in nursing workers? - Dalmolin, Graziele de Lima (2014)
Objective: to identify relationships between moral distress and Burnout in the professional performance from the perceptions of the experiences of nursing workers. Methods: this is a survey type study with 375 nursing workers working in three different hospitals of southern Rio Grande do Sul, with the application of adaptations of the Moral Distress Scale and the Maslach Burnout Inventory, validated and standardized for use in Brazil. Data validation occurred through factor analysis and Cronbach’s alpha. For the data analysis bivariate analysis using Pearson’s correlation and multivariate analysis using multiple regression were performed. Results: the existence of a weak correlation between moral distress and Burnout was verified. A possible positive correlation between Burnout and therapeutic obstinacy, and a negative correlation between professional fulfillment and moral distress were identified. Conclusion: the need was identified for further studies that include mediating and moderating variables that may explain more clearly the models studied.